Acute immune thrombocytopenic purpura - Bolton-Maggs, P. (Hämostaseologie, 2009)
Immune thrombocytopenia in children is usually a self-limiting illness, but in adults the disease is likely to be chronic, and may be associated with other pathology which predisposes to bleeding. Despite very low platelet counts serious bleeding is rare in both adults and children. More than 80% of children have mild clinical manifestations. Intracranial haemorrhage is rare at all ages, is unpredictable and can occur at any time when the count is very low. Currently recommended therapies for both adults and children are associated with significant side effects and occasional deaths. Treatment may interfere with quality of life more than the illness itself. Drugs can be withheld in the majority of children with appropriate advice to child and family. Treatment can be individualised, taking into account the person’s needs and lifestyle as well as bleeding. In chronic ITP many need no active therapy. The situation with adults is more complex but those with a platelet count above 30 x 109/l usually need no treatment as bleeding is rare, and those adults with refractory ITP unresponsive to treatment live with very low counts for years without significant bleeding suggesting the need to re-evaluate the balance of risks of treatment versus bleeding. It is notable that adults with ITP may die from infection, probably related to therapy.
Keywords: ITP; thrombocytopenia